Formation of Spinel Phases in Oxidized BOF Slag under Different Cooling Conditions. Issue 11 (14th June 2017) - Jiang, Liang; Bao, Yiwang; Yang, Qixing; Chen, Yuhong; Liu, Guiqun; Han, Fenglan; Wei, Jie; Engström, Fredrik; Deng, Jiangyuan
Abstract : To enhance utilization of wastes generated from steelmaking, a BOF slag sample from Ning Steel group in China is treated by oxidizing at 1500 °C for 30 min and then cooled by different methods. The treated samples are characterized, in combination with calculations using FactSage 6.4. XRD results show that iron oxides in BOF slag are converted largely by the oxidation to spinel phases, Fe3 O4 and MgFe2 O4, which also eliminates free CaO and MgO. EDS analyses show Fe element existing in di‐calcium silicate and glass phase, which are Fe 3+ ions formed by oxidation. An incorporation of Fe 3+ ions into crystal structures has stabilized high temperature polymorph of C2 S, β‐C2 S, and α'‐C2 S, in the treated slag samples. Fe 3+ ions may also act as a network former to facilitate glass formation. This may make it possible for the glass and α'‐C2 S phase to complement each other, leading to a higher hydraulicity, while the BOF slag, after the spinel separation, is blended in cements. Some suggestions are proposed, based on the present and early studies, to enhance hydraulicity for the BOF slag, as well as grain sizes of spinel phases, which may result in economic and environmental benefits for steel and cement industries. Abstract : A BOF slag sample from Ning Steel group in China is treated by oxidizing at 1500 °C for 30 min and subsequently cooled by either water or air, as well as in the furnace. The treated samples are characterized together with some related equilibrium calculations with suggestions proposed to enhance the slag recycling.